Creating the congruent workplace : challenges for people and their organizations - Williams, Lloyd C. (Quorum Books, 2002)
A call for thought balanced against action in the development of programs for organizational change, and a persuasive warning against compartmentalization and other mistakes that too often lead organizations to innovate themselves into failure. For organizational and personal change to happen and be sustainable, there must first be a system of thought balanced against action. Williams and his concept of "congruence" provide an alternative to the often chaotic, unbalanced ways in which change is currently understood and its accomplishment attempted. He challenges the organizational model of compartmentalized structures, offers a persuasive refutation of the fashionable paradigm of organizational transformation (one based on dominance and control), and argues a provocative notion that innovation is actually the successful result of reworking what has not worked before. A new look at the processes that create organizational movement, Williams' latest book is a guide for leaders, managers, consultants, and corporate practitioners, and a new way for students, teachers, and researchers to rethink the entire change process.; Williams has found through his own experience that people focus too closely on the "action" behaviors of organizations and too little on the thinking behind them. The result is that gaps open up and create pitfalls in our efforts to achieve excellence in human and organizational performance. Williams suggests that organizations innovate themselves into failure. To counter this, he provides a true systemic approach to enhancing organizational performance, a system of what he visualizes as "congruence," a way to fit thoughts to actions. It is as much a way of thinking, says Williams, as it is a method toward goals--goals that are clear and essential to the survival of any organization. Drawing liberally upon his own expertise as a teacher, consultant, and therapist, he helps others to appreciate the successes that can be realized when balance and the alignment of thought and action are achieved, and when the search for change becomes a planned, focused, and systemic endeavor